Ural Economy of The XX Century by Historians’ - Zapariy, Vladimir Vasilievich; Kamynin, Vladimir Dmitrievich; Guanshan, Chzhan (Economy of Regions, 2015)
In the article, the most prominent works of the Ural scientists in economic history for the last decades are considered. Stages of development of research interest of historians and economists in this issue are allocated. On the example of these works, the authors of the article draw a theoretical conclusion that there is a growth of interest in economic history due to the development of multimethodological approach of scientists, rapprochement of positions of representatives of these sciences. The history is useful for every scientist-economist not only as a storeroom of the economic facts checked by life and collection of experiments testing economic science in all directions but also it is very important as a source of economic ideas. There are authentic cross-cultural communications revealing in mutual use by representatives of historical and economic science of the explaining theories developed within each of the scientific disciplines. For the present stage of the economic history, research of Ural, the unstudied issues by historical science for the objective causes are the most relevant. These are the issues like prohibition of the use of sources because of topics’ secrecy, an existence of non-disclosure subjects, undesirable subjects in works on national history. In the article, development problems in the economy of Ural of the branch, territorial and production complexes earlier investigated mainly by representatives of economic science are considered. Research of economic history is characterized by the new scientific issues, development of source base, application to a research of various methodological bases, use of the conceptual approaches and methods of research developed in foreign and national economic science.